Superhydrophobic PVDF membrane formed by crystallization process for direct contact membrane distillation - Caiyun Hou; Lei Du; Yao Li; Meiwei Guo; Jiti Zhou; Sen Qiao (iScience, 2023)
Summary: With growing demand for freshwater resources, membrane distillation (MD) attracts intensive attention owing to the possibility of reclaiming almost 100% freshwater with superhydrophobic membranes as the pivotal separation units. Current superhydrophobic membrane still suffers relatively complex preparation process and limited membrane flux. Herein, we developed a promising route to fabricate a high-flux superhydrophobic poly(vinylidene fluoride) (PVDF) membrane by a simple solute and solvent co-crystallization (SSCC) method, which endowed the membrane ultra-high porosity and flux. We also found that the pore size of superhydrophobic membrane can be adjusted by controlling the crystallization process of DMSO, which gave rise to membrane higher flexibility. The membrane exhibited the outperforming desalination performance even in multiple harsh environments including different temperature, salty concentration, and pH, with/without humic acid. The membrane also displayed distinguished anti-fouling performance and long-term stability, which is quite significant for practical application.